Inflammation in MASLD progression and cancerKey points: - Yeonsoo Kim; Yunseo Park; Hyunsoo Rho; Tiantian Yao; Bin Gao; Seonghwan Hwang (JHEP Reports)
Summary: Steatotic liver diseases include metabolic dysfunction-associated steatotic liver disease (MASLD), alcohol-associated liver disease, and metabolic dysfunction and alcohol-related liver disease (MetALD), encompassing a spectrum of metabolic liver disorders that range from steatosis to steatohepatitis, cirrhosis, and hepatocellular carcinoma. Steatotic liver disease is primarily driven by alcohol consumption and metabolic dysfunction, making it the leading cause of chronic liver disease. Steatosis is defined by excessive fat accumulation in the liver without significant liver injury or inflammation. In contrast, inflammation is the predominant factor that drives the progression of steatosis to steatohepatitis and, ultimately, to cancer. In this review, we summarise the current understanding of the inflammatory mechanisms underlying the pathogenesis of MASLD and explore molecular targets that may offer the potential for pharmacological intervention. Additionally, given the pathological similarities between MASLD and MetALD, relevant inflammatory pathways in MetALD are briefly discussed to underscore both commonalities and key distinctions between the two conditions.